1999
DOI: 10.1046/j.1365-3156.1999.00416.x
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic PCR with Leishmania donovani specificity using sequences from the variable region of kinetoplast minicircle DNA

Abstract: SummaryKala azar or visceral leishmaniasis, a parasitic disease caused by Leishmania donovani, is presently causing an epidemic in the eastern region of India. Diagnosis of kala azar is often complicated. We developed a pair of oligonucleotides suitable as primers from the variable region of a predominant sequence class of minicircles of L. donovani. These primers were used in a nonisotopic polymerase chain reaction and found to be highly specific for the parasites of L. donovani complex. Using these primers, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 11 publications
(9 reference statements)
2
22
0
Order By: Relevance
“…Use of peripheral blood is advantageous because the collection procedure is less invasive and safer than the splenic or bone marrow biopsy specimen collection. In earlier studies for diagnosis of VL due to L. donovani, the sensitivity of PCR for blood samples has been found to be in the range of 45 to 94% based on smaller sample sizes ranging from 17 to 42 (1,4,15,21,22,32,35). For detection of VL due to L. donovani infantum, which may have a different pathogenesis, sensitivities between 64 to 97% have been reported with blood samples (16,18,21).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Use of peripheral blood is advantageous because the collection procedure is less invasive and safer than the splenic or bone marrow biopsy specimen collection. In earlier studies for diagnosis of VL due to L. donovani, the sensitivity of PCR for blood samples has been found to be in the range of 45 to 94% based on smaller sample sizes ranging from 17 to 42 (1,4,15,21,22,32,35). For detection of VL due to L. donovani infantum, which may have a different pathogenesis, sensitivities between 64 to 97% have been reported with blood samples (16,18,21).…”
Section: Discussionmentioning
confidence: 99%
“…PCR products were analyzed in 1% agarose gel, and Southern blot analysis was done as described (14). Southern blots were hybridized with 32 P-labeled cloned L. donovani kDNA fragments using the conditions described (14).…”
Section: Methodsmentioning
confidence: 99%
“…There are different target sequences used, which include ribosomal RNA genes, kinetoplast DNA (kDNA), miniexon-derived RNA (medRNA), and the β-tubulina gene region [103].…”
Section: Molecular Methods: Polymerase Chain Reaction (Pcr)mentioning
confidence: 99%
“…The ideal sample is peripheral blood due to its non-invasive character. Using peripheral blood, the sensitivity ranges described vary from 70% to 100% [93,102,103].…”
Section: Molecular Methods: Polymerase Chain Reaction (Pcr)mentioning
confidence: 99%
“…Several studies have reported that qPCR has virtually no false positive results . Cases where qPCR had specificity lower than 1.0 were attributed to contamination of the respective biological specimens or reagents, or/and the absence of good gold standard for reference . This is therefore one of the diagnostic tests for which it is appropriate to use the method we have presented.…”
Section: Discussionmentioning
confidence: 86%